Inherited Exile and the Work of María Rosa Lojo - Marcela Crespo Buiturón (Studies in 20th & 21st Century Literature, 2011)
In recent decades, Argentine literature has demonstrated increasing interest not in Spanish immigrants or exiles but rather in their children, prompting a reconsideration of critical approaches to exile to account for situations in which the same experience acts as a mirror between parents and the children who inherit exile from them. The work and the reflections of the poet, essayist and narrative writer María Rosa Lojo, daughter of exiles—a Spanish Republican father and Francoist mother—in Buenos Aires, can be considered a paradigmatic example.
Keywords: María Rosa Lojo; Argentine literature; exile; mirror; parents; children; immigrants; immigration